Production and Optimisation of Tetracycline by Various Strains of Streptomyces under Solid State Fermentation using Pineapple Peel as a Novel Substrate - E. Neelagund2, Basavaraj M. Vastrad1 and Shivayageeswar (Recent Research in Science and Technology, 2011)
Pineapple peel is the principal solid waste product of the juice processing industry. The disposal of the fresh peels is becoming a major problem to many food processing industries. Dry pineapple peels are rich in biodegradable organic material and suspended solids; therefore, this waste was used as a novel substrate in present solid substrate fermentation. The effect of medium ingredients such as carbon, inorganic and organic nitrogen sources, inorganic salts on tetracycline production by various strains of Streptomyces [S. aureofaciens NCIM (2417, 2614, 2615), S. rimosus Â NCIM 2213 and S. viridifaciens NCIM 2506] in solid-state fermentations (SSF) was observed. The 1.0-fold lower antibiotic yield than the control in the presence of glucose and sucrose in SSF at 10% w/w was observed , whereas peanut meal and ammonium sulphate was found to be a more favorable organic and inorganic nitrogen source than the control in SSF at 10% and 1% w/w. Calcium carbonate (CaCO3) as inorganic salt favored 0.5% higher antibiotic yield than the control at 1% w/w. Various crucial parameters such as initial moisture content, incubation temperature, initial pH, substrate particle size and inoculum size were derived; 65% moisture level, 35oC temperature, pH 5-0-6.5, 6 x 4 mm particle size and (1.0 x 108 spores/ ml) inoculum size was found to be suited for maximal tetracycline production. The maximum tetracycline production was observed following 3â€“7 days of fermentation cycle.